Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

CubeSat constellation shines light on fisheries studies: A case study of fish mortality events - Lin Qi; Menghua Wang; Jennifer Cannizzaro; Chuanmin Hu (Remote Sensing Applications: Society and Environment, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Coral reef terrace age deduced from retreating knickpoints - Yiran Wang; Aron J. Meltzner; Michael E. Oskin; Jennifer Quye-Sawyer; Lin Thu Aung; Noelynna Ramos (Earth and Planetary Science Letters, 2026)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Detection of unusually high transcriptomic and proteomic abundance of bromoform-synthesizing halogenase in marine macroalgae Asparagopsis taxiformis - Zhenjian Lin; Shahima Islam; Matthew S. Hargrave; Rakesh Singh; Lingjie Zhou; Ramon Xie; Jennifer E. Smith; Eric W. Schmidt; Vinayak Agarwal (Frontiers in Marine Science, 2025)
Halogenated molecules produced by marine algae are thought to be defensive secondary metabolites. The extraordinarily high concentration of bromoform in the seaweed Asparagopsis —up to 8% dry tissue weight—challenges the exclusivity of this paradigm. In this report, we provide evidence that the mbb1 gene which encodes the bromoform producing halogenase is among the most highly transcribed genes in Asparagopsis tissue, with the resulting Mbb1 protein abundance rivaling that of enzymes involved in photosynthesis and carbon fixation. When the seaweed was stressed with light, transcripts for both mbb1 and for proteins involved in photosynthesis were significantly downregulated. Conversely, heat stress modestly upregulated some photosynthesis genes but had no impact on mbb1 . Taken together, these findings allow us to posit that bromoform production is not solely a stress-response or self-defense mechanism for A. taxiformis . Instead, we propose that the halogenase Mbb1 likely fulfils a primary metabolic function in this red alga thusly reconceptualizing halogenation biochemistry and pulling it out of the domain of natural product biosynthesis alone.

Rankings of tuberculosis antibiotic treatment regimens are sensitive to spatial scale, detection limit, and initial host bacterial burden - Christian T. Michael; Maral Budak; Pauline Maiello; Kara Kracinovsky; Mark Rodgers; Jaime Tomko; Philana Ling Lin; JoAnne Flynn; Jennifer J. Linderman; Denise Kirschner (Journal of Theoretical Biology, 2025)

Sphagnum cultivation enhances soil carbon stock by alleviating microbial phosphorus limitation - Dan Xue; Huai Chen; Xiaohan Yang; Jennifer Ene Idoko; Lin Wu (Agriculture, Ecosystems & Environment, 2025)

Uplift, tilting, and underlying structures of coastal northwestern Luzon, Philippines, deduced from marine terraces - Yiran Wang; Aron J. Meltzner; Jennifer Quye-Sawyer; Huili Yang; Yichen Pu; Jintang Qin; Lin Thu Aung; Zihan Aw; Andrea Denise A. Pamintuan; Noelynna T. Ramos (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

Residue depletion profiles and withdrawal intervals of florfenicol and its metabolite florfenicol amine in plasma and milk of lactating goats after repeated subcutaneous administrations - Qiran Chen; Zhoumeng Lin; Jennifer L. Davis; Emily Toney; Maaike O. Clapham; Xue Wu; Lisa A. Tell (Regulatory Toxicology and Pharmacology, 2024)

The role of perceived negative partner behavior in daily snacking behavior: A dynamical systems approach - Jingrun Lin; Jennifer K. MacCormack; Steven M. Boker; James A. Coan; Sarah C.E. Stanton (Appetite, 2024)

Evaluation of spatial and temporal changes in illicit drug use in the Taipei metropolitan area via wastewater-based epidemiology - Hank Hui-Hsiang Lin; Yu-Hsiang Wang; Jennifer Ia Wen Wen Liu; Ming-Chi Hsieh; Shu-Jie Huang; En Lien; Li-Wei Huang; Angela Yu-Chen Lin (Science of The Total Environment, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Geological controls on lithium production from basinal brines across North America - Mohammad Marza; Grant Ferguson; Jon Thorson; Isabel Barton; Ji-Hyun Kim; Lin Ma; Jennifer McIntosh (Journal of Geochemical Exploration, 2024)

Pharmacokinetics, tissue residue depletion, and withdrawal interval estimations of florfenicol in goats following repeated subcutaneous administrations - Xue Wu; Zhoumeng Lin; Emily Toney; Maaike O. Clapham; Scott E. Wetzlich; Jennifer L. Davis; Qiran Chen; Lisa A. Tell (Food and Chemical Toxicology, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

A risk-based approach to cumulative effects assessment for large marine ecosystems to support transboundary marine spatial planning: A case study of the yellow sea - Chen Ma; Vanessa Stelzenmüller; Jennifer Rehren; Jing Yu; Zhiwei Zhang; Hao Zheng; Lu Lin; Hee-Cheol Yang; Yinhuan Jin (Journal of Environmental Management, 2023)

Development of machine learning algorithms to estimate maximum residue limits for veterinary medicines - Nader Zad; Lisa A. Tell; Remya Ampadi Ramachandran; Xuan Xu; Jim E. Riviere; Ronald Baynes; Zhoumeng Lin; Fiona Maunsell; Jennifer Davis; Majid Jaberi-Douraki (Food and Chemical Toxicology, 2023)

Shifts in the composition of nitrogen deposition in the conterminous United States are discernable in stream chemistry - Meredith G. Lassiter; Jiajia Lin; Jana E. Compton; Jennifer Phelan; Robert D. Sabo; John L. Stoddard; Stephen R. McDow; Tara L. Greaver (Science of The Total Environment, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

The thermal degradation and soil recovery of thermal treatment of field-weathered decabrominated diphenyl ether-contaminated soil - Jennifer Ia Wen Wen Liu; Yu-Jie Lin; Chi-Fong Ko; Jiann-yuan Ding; Yang-hsin Shih (Chemosphere, 2023)

Longitudinal measurements of per- and poly-fluoroalkyl substances (PFAS) in archived human serum samples between 1975 and 1995 in Australia - Sandra Nilsson; Jennifer Bräunig; Renee N. Carey; Jennie Hui; Kayla Smurthwaite; Leisa-Maree Toms; Martyn D. Kirk; Jochen F. Mueller; Lin Fritschi (Journal of Hazardous Materials, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Simulations of rate of genetic gain in dry bean breeding programs - Jennifer Lin; Vivi Arief; Zulfi Jahufer; Juan Osorno; Phil McClean; Diego Jarquin; Valerio Hoyos-Villegas (Theoretical and Applied Genetics, 2023)
Key message A reference study for breeders aiming at maximizing genetic gain in common bean. Depending on trait heritability and genetic architecture, conventional approaches may provide an advantage over other frameworks. Abstract Dry beans ( Phaseolus vulgaris L.) are a nutrient dense legume that is consumed by developed and developing nations around the world. The progress to improve this crop has been quite steady. However, with the continued rise in global populations, there are demands to expedite genetic gains. Plant breeders have been at the forefront at increasing yields in the common bean. As breeding programs are both time-consuming and resource intensive, resource allocation must be carefully considered. To assist plant breeders, computer simulations can provide useful information that may then be applied to the real world. This study evaluated multiple breeding scenarios in the common bean and involved five selection strategies, three breeding frameworks, and four different parental population sizes. In addition, the breeding scenarios were implemented in three different traits: days to flowering, white mold tolerance, and seed yield. Results from the study reflect the complexity of breeding programs, with the optimal breeding scenario varying based on trait being selected. Relative genetic gains per cycle of up to 8.69% for seed yield could be obtained under the use of the optimal breeding scenario. Principal component analyses revealed similarity between strategies, where single seed descent and the modified pedigree method would often aggregate. As well, clusters in the direction of the Hamming distance eigenvector are a good indicator of poor performance in a strategy.

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Correction to: R-praziquantel integrated population pharmacokinetics in preschool- and school-aged African children infected with Schistosoma mansoni and S. haematobium and Lao adults infected with Opisthorchis viverrini - Christine Falcoz; Serge Guzy; Jana Kovač; Isabel Meister; Jean Coulibaly; Somphou Sayasone; David Wesche; Yu-Wei Lin; Jennifer Keiser (Journal of Pharmacokinetics and Pharmacodynamics, 2022)

R-praziquantel integrated population pharmacokinetics in preschool- and school-aged African children infected with Schistosoma mansoni and S. haematobium and Lao adults infected with Opisthorchis viverrini - Christine Falcoz; Serge Guzy; Jana Kovač; Isabel Meister; Jean Coulibaly; Somphou Sayasone; David Wesche; Yu-Wei Lin; Jennifer Keiser (Journal of Pharmacokinetics and Pharmacodynamics, 2022)

A geochemical and isotopic assessment of hydraulic connectivity of a stacked aquifer system in the Lisbon Valley, Utah (USA), and critical evaluation of environmental tracers - Chandler Noyes; Jihyun Kim; Mark Person; Lin Ma; Grant Ferguson; Jennifer C. McIntosh (Hydrogeology Journal, 2021)

Patterns of chronic disease management and health outcomes in a population-based cohort of Black women with breast cancer - Michelle Doose; Jennifer Tsui; Michael B. Steinberg; Cathleen Y. Xing; Yong Lin; Joel C. Cantor; Chi-Chen Hong; Kitaw Demissie; Elisa V. Bandera (Cancer Causes & Control, 2021)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Metabolomics profiling of visceral and abdominal subcutaneous adipose tissue in colorectal cancer patients: results from the ColoCare study - Jennifer Ose; Andreana N. Holowatyj; Johanna Nattenmüller; Biljana Gigic; Tengda Lin; Caroline Himbert; Nina Habermann; David Achaintre; Augustin Scalbert; Pekka Keski-Rahkonen; Jürgen Böhm; Petra Schrotz-King; et al. (Cancer Causes & Control, 2020)

Waiting and “weighted down”: the challenge of anticipatory loss for individuals and families with Li-Fraumeni Syndrome - Allison Werner-Lin; Jennifer L. Young; Catherine Wilsnack; Shana L. Merrill; Victoria Groner; Mark H. Greene; Payal P. Khincha (Familial Cancer, 2020)

The role of soil redox conditions in microbial phosphorus cycling in humid tropical forests - Avner Gross; Yang Lin; Peter K. Weber; Jennifer Pett‐Ridge; Whendee L. Silver (Ecology, 2020)
Humid tropical forests are among the most productive ecosystems globally, yet they often occur on soils with high phosphorus (P) sorption capacity, lowering P availability to biota. Short‐term anoxic events are thought to release sorbed P and enhance its acquisition by soil microbes. However, the actual effects of anoxic conditions on microbial P acquisition in humid tropical forest soils are surprisingly poorly studied. We used laboratory incubations of bulk soils, NanoSIMS analysis of single microbial cells, and landscape‐scale measurements in the Luquillo Experimental Forest (LEF), Puerto Rico to test the hypothesis that anoxic conditions increase microbial P acquisition in humid tropical forests. In laboratory and field experiments, we found that microbial P uptake generally decreased under anoxic conditions, leading to high microbial carbon (C) to P ratios in anoxic soils. The decreased P acquisition under anoxic conditions was correlated with lower microbial C use efficiency (CUE), an index of microbial energy transfer in ecosystems. Phosphorus amendments to anoxic soils led to increased microbial P uptake and higher CUE suggesting that microbes were less able to access and utilize P under natural low redox conditions. Under oxic conditions, microbial C:P ratios and CUE did not respond to changes in substrate stoichiometry. These results challenge the existing paradigm by showing that anoxic conditions can decrease microbial P uptake and ultimately constrain microbial CUE. Our findings indicate that soil redox conditions tightly couple soil P and C cycles and advance our understanding of controls on P cycling in humid tropical forest ecosystems.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Integration of Food Animal Residue Avoidance Databank (FARAD) empirical methods for drug withdrawal interval determination with a mechanistic population-based interactive physiologically based pharmacokinetic (iPBPK) modeling platform: example for flunixin meglumine administration - Miao Li; Yi-Hsien Cheng; Jason T. Chittenden; Ronald E. Baynes; Lisa A. Tell; Jennifer L. Davis; Thomas W. Vickroy; Jim E. Riviere; Zhoumeng Lin (Archives of Toxicology, 2019)

Long-term Nutrient Fertilization Increased Soil Carbon Storage in California Grasslands - Yang Lin; Eric W. Slessarev; Scott T. Yehl; Carla M. D’Antonio; Jennifer Y. King (Ecosystems, 2019)

Lifetime recreational physical activity and the risk of prostate cancer - Elizabeth Sorial; Si Si; Lin Fritschi; Ellie Darcey; Justine E. Leavy; Jennifer Girschik; Gina L. Ambrosini; Terry Boyle (Cancer Causes & Control, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Endocrine-Disrupting Activities and Organic Contaminants Associated with Oil and Gas Operations in Wyoming Groundwater - Christopher D. Kassotis; Danh C. Vu; Phuc H. Vo; Chung-Ho Lin; Jennifer N. Cornelius-Green; Sharyle Patton; Susan C. Nagel (Archives of Environmental Contamination and Toxicology, 2018)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Microbial manganese(III) reduction fuelled by anaerobic acetate oxidation - Nadia Szeinbaum; Hui Lin; Jay A. Brandes; Martial Taillefert; Jennifer B. Glass; Thomas J. DiChristina (Environmental Microbiology, 2017)
Summary Soluble manganese in the intermediate +III oxidation state (Mn 3+ ) is a newly identified oxidant in anoxic environments, whereas acetate is a naturally abundant substrate that fuels microbial activity. Microbial populations coupling anaerobic acetate oxidation to Mn 3+ reduction, however, have yet to be identified. We isolated a Shewanella strain capable of oxidizing acetate anaerobically with Mn 3+ as the electron acceptor, and confirmed this phenotype in other strains. This metabolic connection between acetate and soluble Mn 3+ represents a new biogeochemical link between carbon and manganese cycles. Genomic analyses uncovered four distinct genes that allow for pathway variations in the complete dehydrogenase‐driven TCA cycle that could support anaerobic acetate oxidation coupled to metal reduction in Shewanella and other Gammaproteobacteria. An oxygen‐tolerant TCA cycle supporting anaerobic manganese reduction is thus a new connection in the manganese‐driven carbon cycle, and a new variable for models that use manganese as a proxy to infer oxygenation events on early Earth.

Interactions of early adversity with stress-related gene polymorphisms impact regional brain structure in females - Arpana Gupta; Jennifer Labus; Lisa A. Kilpatrick; Mariam Bonyadi; Cody Ashe-McNalley; Nuwanthi Heendeniya; Sylvie Bradesi; Lin Chang; Emeran A. Mayer (Brain Structure and Function, 2016)

A Role for Low Density Lipoprotein Receptor-Related Protein 1 in the Cellular Uptake of Tissue Plasminogen Activator in the Lungs - Swan Lin; Jennifer Racz; Melissa F. Tai; Kristina M. Brooks; Phillip Rzeczycki; Lauren J. Heath; Michael W. Newstead; Theodore J. Standiford; Gus R. Rosania; Kathleen A. Stringer (Pharmaceutical Research, 2016)

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study - Danny V. Colombara; Lisa E. Manhart; Joseph J. Carter; Stephen E. Hawes; Noel S. Weiss; James P. Hughes; Matt J. Barnett; Gary E. Goodman; Jennifer S. Smith; You-Lin Qiao; Denise A. Galloway (Cancer Causes & Control, 2015)

Effects of UV photodegradation on subsequent microbial decomposition of Bromus diandrus litter - Yang Lin; Rachel D. Scarlett; Jennifer Y. King (Plant and Soil, 2015)

Association between plasma adiponectin levels and colorectal cancer risk in women - Paulette D. Chandler; Julie E. Buring; JoAnn E. Manson; M. V. Moorthy; Shumin Zhang; I-Min Lee; Jennifer H. Lin (Cancer Causes & Control, 2015)

Application of Physiologically Based Absorption Modeling to Formulation Development of a Low Solubility, Low Permeability Weak Base: Mechanistic Investigation of Food Effect - Hefei Zhang; Binfeng Xia; Jennifer Sheng; Tycho Heimbach; Tsu-Han Lin; Handan He; Yanfeng Wang; Steven Novick; Ann Comfort (AAPS PharmSciTech, 2014)

Effects of UV Exposure and Litter Position on Decomposition in a California Grassland - Yang Lin; Jennifer Y. King (Ecosystems, 2014)

Mutant strains of Pichia pastoris with enhanced secretion of recombinant proteins - Sasha Larsen; Jun Weaver; Katherine de Sa Campos; Rhobe Bulahan; Jackson Nguyen; Heather Grove; Amy Huang; Lauren Low; Namphuong Tran; Seth Gomez; Jennifer Yau; Thomas Ilustrisimo; et al. (Biotechnology Letters, 2013)

Utility of Physiologically Based Modeling and Preclinical In Vitro/In Vivo Data to Mitigate Positive Food Effect in a BCS Class 2 Compound - Binfeng Xia; Tycho Heimbach; Tsu-han Lin; Shoufeng Li; Hefei Zhang; Jennifer Sheng; Handan He (AAPS PharmSciTech, 2013)

Quantitative exposure metrics for sleep disturbance and their association with breast cancer risk - Jennifer Girschik; Lin Fritschi; Thomas C. Erren; Jane Heyworth (Cancer Causes & Control, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Rapid decrease in tumor perfusion following VEGF blockade predicts long-term tumor growth inhibition in preclinical tumor models - Alexandra Eichten; Alexander P. Adler; Blerta Cooper; Jennifer Griffith; Yi Wei; George D. Yancopoulos; Hsin Chieh Lin; Gavin Thurston (Angiogenesis, 2013)

Influences of Zero-Valent Sulfur on Mercury Methylation in Bacterial Cocultures - Rita A. Kampalath; Chu-Ching Lin; Jennifer A. Jay (Water, Air, & Soil Pollution, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Evaluation of Candidate Gene Effects for Beef Backfat via Bayesian Model Selection - Xiao-Lin Wu; Michael D. MacNeil; Sachinadan De; Qian-Jun Xiao; Jennifer J. Michal; Charles T. Gaskins; Jerry J. Reeves; Jan R. Busboom; Raymond W. Wright; Zhihua Jiang (Genetica, 2005)

Risk of non-Hodgkin lymphoma associated with occupational exposure to solvents, metals, organic dusts and PCBs (Australia) - Lin Fritschi; Geza Benke; Ann M. Hughes; Anne Kricker; Claire M. Vajdic; Andrew Grulich; Jennifer Turner; Samuel Milliken; John Kaldor; Bruce K. Armstrong (Cancer Causes & Control, 2005)

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

Differences in the distribution of synemin, paranemin, and plectin in skeletal muscles of wild-type and desmin knock-out mice - Lena Carlsson; Zhen Lin Li; Denise Paulin; Maureen G. Price; Jennifer Breckler; Richard M. Robson; Gerhard Wiche; Lars-Eric Thornell (Histochemistry and Cell Biology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)